POTRET TOLERANSI ANTAR UMAT BERAGAMA DI SEKOLAH MENENGAH KEJURUAN NEGERI 2 MALANG - Muhammad Rizal Miftahul Huda; Chalimah Sa’dijah; Fita Mustafida (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Tolerance in Islam is an important message. Because Indonesia is a unitary state, there are religious diversity etc. This is the context for conducting research on religious tolerance. The researcher focuses on the forms and practices of tolerance as well as the factors that support and hinder the practice of religious tolerance at SMKN2 Malang. This study uses a qualitative approach using a kind of phenomenology. This survey will be conducted from May 20, 2021 to June 20, 2021. This survey is intended for teachers, employees, and students. Data collection techniques through observation, interviews and documents. Data analysis techniques with horizontal analysis methods, explanations of structures, explanations of structures, explanations of the meaning of phenomena. The data validation method then looks at persistence, triangulation, increased participation, and ends with peer discussion. The survey results are as follows. (1) Form and implementation of religious tolerance: religious freedom permit, religious freedom, inter-religious cooperation permit. Religious community. (2) A school environment that promotes religious tolerance, a factor that supports school activities that respect religious differences. No retention factor, but far from ideal.” Kata Kunci: Beragama, Toleransi